Analysis of optimized multilevel matrix converter for DFIG based wind energy conversion system - Shubha Baravani; Rudranna Nanadihalli; Mohsin A. Mulla (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Wind power generation is an increasing trend worldwide. Multilevel converters in this regard are playing an essential role in high power system applications due to various features. In this paper, multi-objective optimization based multilevel matrix converter (MOMMC) is proposed for wind energy conversion system. The assessment of feasibility through the discussion of two objectives: reliability and cost have been considered in this study. Initially, the model of the two objectives is assessed against redundancy configuration and power loss. Then a multi-objective function is defined for achieving low cost and high reliability. The optimal topology for the matrix multi-level converter is determined using the membership function, and the solution is selected from the Pareto-optimal set. The reliability and cost analysis of the proposed MOMMC is performed. Simulation is carried out for the proposed multi-objective optimization based multilevel matrix converter using the PSIM software. To establish the validity of the proposed method, two different cases: 1) fixed and 2) variable speed of 9 MW doubly-fed induction generator-based wind energy system are considered. The results show the superiority of the proposed method over the others.